“Come Rap for the Planet”: Matters of Life and Death in Nadine Gordimer’s Get a Life (2005) - Szczurek, Karina Magdalena (Department of Dutch and South African Studies, Faculty of English, 2009)
Get a Life (2005) is Nadine Gordimer’s latest and probably last novel. As some of its reviewers have suggested, it is not a major addition to her oeuvre. However, its significance lies in its activist thrust as the first truly ‘green’ novel published in postapartheid South Africa. Using a basic ecocritical approach, the following essay exposes the eco-conscious character of the book. Furthermore, it shows how the novel engages in some crucial contemporary debates in the South African public sphere and situates them in the global context of the 21st century. At the same time, by looking at some of Gordimer’s short stories written around the time of publication of Get a Life and primarily at the novel itself, this essay analyses how the author explores the topics of ageing and natural death as well as the need to leave a trace of one’s life beyond physical existence.
Keywords: ecocriticism, and society; post-apartheid literature; globalisation; confrontation with ageing and death